EU Regulatory Risk Management of Marine Biotoxins in the Marine Bivalve Mollusc Food-Chain - Micheál O’Mahony (Toxins, 2018)
Food safety risk assessment in the European Union (EU) recognises consumer illness that arises from marine biotoxins as a risk associated with bivalve mollusc consumption. EU food regulations contain various general food safety obligations, which should contribute significantly to managing this risk. EU food regulations additionally impose various specific obligations on both Food Business Operators and Competent Authorities in order to manage the marine biotoxin food safety risk in the bivalve mollusc food-chain. These have a particular focus on the pre-harvest component of the food-chain. A central component of these specific systems is the requirement for ongoing monitoring of phytoplankton and biotoxin concentrations in water and molluscs, respectively. This monitoring explicitly brings a potential outcome of closing production areas delineated by classification to prohibit the harvest of bivalve molluscs as food from those areas when acceptable biotoxin concentrations are exceeded. This review considers the utility of these systems, at conceptual and practical levels, and explores their contribution to an effective regulatory risk management approach.